Unusual association between lysinuric protein intolerance and moyamoya vasculopathy. (September 2016) - Ghilain, Valérie; Wiame, Elsa; Fomekong, Edward; Vincent, Marie-Françoise; Dumitriu, Dana; Nassogne, Marie-Cécile
Abstract: Introduction: Lysinuric protein intolerance (LPI) is a form of inherited aminoaciduria caused by a deficiency in the cationic amino acid transport process on the basolateral membrane of enterocytes and renal tubular cells. Clinical signs include gastrointestinal symptoms, failure to thrive, hepatosplenomegaly, osteoporosis, episodes of coma, intellectual deficiency, lung and renal involvement, bone marrow abnormalities, as well as altered immune response. Moyamoya disease is a cerebrovascular disorder predisposing sufferers to stroke through progressive stenosis of the intracranial internal carotid arteries and their proximal branches. Patients with characteristic moyamoya vasculopathy who also exhibit well-recognized associated conditions, such as Down syndrome or sickle-cell disease, are diagnosed with moyamoya syndrome, whereas those with no known associated risk factors are said to suffer from moyamoya disease. Case study: A 5-year-old girl exhibiting aversion to protein-rich food and splenomegaly presented with a history of recurrent ischemic strokes. Cerebral angiography confirmed moyamoya vasculopathy. Metabolic investigation revealed abnormalities characteristic of LPI. This diagnosis was confirmed by the detection of a mutation within the SLC7A7 gene upon molecular investigation. Conclusion: To the best of our knowledge, this is the first reported case of an association between moyamoya vasculopathy and LPI. While the question of association or coincidence cannot yet be answered, several pathophysiological consequences of LPI can be defined as separate, such as links between the impact of low arginine levels on the function of vascular endothelium and brain nitric oxide metabolism, as well as hemophagocytic syndrome associated with the risk of vasculitis, thus accounting for the development of moyamoya vasculopathy. Highlights: This unusual association between momoya vasculopathy and a rare metabolic disease suggests some pathophysiological mechanisms.